Acute Kidney Injury in Pregnancies Complicated by Late-Onset Preeclampsia with Severe Features - Rodriguez, Aldeboran N.; Nelson, David B.; Spong, Catherine Y.; McIntire, Donald D.; Reddy, Meghana T.; Cunningham, F. Gary (American Journal of Perinatology, 2022)
Objectives Acute kidney injury (AKI)-complicating pregnancy is used as a marker of severe maternal morbidity (SMM) and frequently associated with obstetric hypertensive disorders. We examined AKI in pregnancies complicated by late-onset preeclampsia with severe features (SPE) using the Kidney Disease: Improving Global Outcomes (KDIGO) criteria. We compared outcomes of pregnancies with and without AKI and stratified by stage of disease. We further differentiated renal dysfunction at the time of admission and compared outcomes to those who developed AKI after admission.Study Design This was a retrospective cohort study of women with care established before 20 weeks and diagnosed with preeclampsia with severe features with delivery at ≥34 weeks. Women with chronic hypertension or suspected underlying renal dysfunction were excluded. KDIGO criteria were applied to stratify staging of renal disease. Demographics and perinatal outcomes were compared using Chi-square analysis and Wilcoxon's rank-sum test with p < 0.05 considered significant.Results From January 2015 through December 2019, a total of 3,515 women meeting study criteria were delivered. Of these, 517 (15%) women met KDIGO criteria for AKI at delivery with 248 (48%) having AKI at the time of admission and the remaining 269 (52%) after admission. Stratified by severity, 412 (80%) had stage 1 disease, 89 (17%) had stage II, and 16 (3%) had stage III. Women with AKI had higher rates of cesarean delivery (risk ratio [RR] = 1.3; 95% confidence interval [CI]: 1.17–1.44), postpartum hemorrhage (RR = 1.46; 95% CI: 1.29–1.66), and longer lengths of stay. Other associated outcomes included NICU admission (RR = 1.72; 95% CI: 1.19–2.48), 5-minute Apgar score ≤ 3 (RR = 5.11; 95% CI: 1.98–13.18), and infant length of stay.Conclusion Of women with late preterm SPE, 15% were found to have AKI by KDIGO criteria. The majority (80%) of AKI was stage I disease, and approximately half of the cases were present by the time of admission.Key Points
Keywords: creatinine; hypertensive disorders of pregnancy; KDIGO; perinatal outcomes; postpartum hemorrhage; renal dysfunction; severe maternal morbidity